Outcomes of and factors associated with the development of bronchopulmonary dysplasia with pulmonary hypertension in very low birth weight infants: A retrospective study in a medical center - Chang, Han-Pi; Lien, Reyin; Chu, Shih-Ming; Lin, Jainn-Jim; Chiang, Ming-Chou (Frontiers in Pediatrics, 2023)
Introduction Bronchopulmonary dysplasia (BPD) with pulmonary hypertension (PH) leads to increased morbidity and mortality in extremely preterm infants. Recent studies have analyzed associated factors of PH in BPD; however, it remains inconclusive, and controversy exists regarding the correlation between BPD and PH. This study aims to investigate potential associated factors, clinical characteristics, and outcomes of BPD with pulmonary hypertension in very low birth weight (VLBW) preterm infants. Methods We conducted a retrospective study to review infants with gestational age < 32 weeks and birth weight <1500g admitted to a tertiary neonatal intensive care unit between January 2020 and October 2021 who were diagnosed as moderate to severe BPD. The echocardiogram was performed at postmenstrual age 36 weeks or before discharge. The diagnosis of PH was based on the findings of echocardiogram. Prenatal and postnatal characteristics, demographic data, treatment, and outcomes were collected and analyzed. Results A total of 139 VLBW infants with BPD were enrolled and divided into PH group (n=25) and non-PH group (n=114). The mean gestational age (GA) was 27.3±2.3 weeks and mean birth weight of infants with BPD was 927.3±293.3 grams. A multivariate logistic regression model revealed high PEEP setting (OR 2.105 ;95% CI 1.472-3.011; p<0.001) in established BPD and surgical closure of PDA (OR 6.273; 95% CI 1.574-24.977; p=0.009) were associated with BPD-PH. Neonates with BPD and developed pulmonary hypertension had prolonged hospital stay (p<0.001), longer invasive mechanical ventilation support (p <0.001), retinopathy of prematurity (ROP) (OR 4.201; 95% CI 1.561-11.304; p= 0.003), oxygen support at discharge (OR 5.600; 95% CI 2.175-14.416; p<0.001) and tracheostomy (OR 35.368; 95% CI 4.03-310.43; p<0.001). Conclusion PDA ligation and higher level of PEEP were associated with BPD-PH in our cohort study. Compared with VLBW infants with BPD but without PH, infants with BPD and PH had longer hospitalization, a higher incidence of oxygen support after discharge, ROP and tracheostomy as well.